Chemoprevention of colorectal neoplasia. Issue 12 (21st December 2015) - Wakeman, Chris; Keenan, Jacqueline; Eteuati, Jimmy; Hollington, Paul; Eglinton, Tim; Frizelle, Frank
Abstract: Background: Colorectal cancer is a common and often fatal malignancy. Currently, the modifications that alter disease outcome include early symptom recognition, population screening as well as improved surgical and adjuvant treatments. Preventative strategies have been limited with little evidence that lifestyle changes significantly alter risk. There is however a growing awareness of a potential role for chemoprevention in some patient groups. This study aimed to review the literature associated with chemoprevention in colorectal cancer. Methods: An electronic literature search of MEDLINE and Embase databases was performed on PubMed for studies detailing the use of chemoprevention agents in colon and rectal cancer. The search was limited to clinical trials on adult humans (>16 years of age) published in English since 1990. Results: The strongest evidence is for non‐steroidal anti‐inflammatory drugs slowing polyp progression, notably Sulindac and aspirin in patients with familial adenomatous polyposis and hereditary nonpolyposis colorectal cancer, respectively. There is also increasing evidence that continuing use of low‐dose aspirin reduces long‐term incidence of colorectal cancers. Cyclooxygenase 2 inhibitors also have a potential role but cardiac toxicity currently limits their use. Folic acid, statins, antioxidants, calcium and 5‐aminosalicylic acid lack evidence to support their use at present. Conclusions: Currently, there is not enough evidence to support the implementation of a chemopreventative agent for general use. However, there appears to be a role for aspirin in selected subgroups.